2009
DOI: 10.1111/j.1600-065x.2009.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of inhibiting CD28‐mediated costimulation

Abstract: This volume covers many topics in the field of T-cell costimulation. The need for such a volume is testament to the growth of the field. From its beginning as a concept in the 1980s, we have now progressed to the point where many molecules now have functionally defined roles in T-cell costimulation. In addition, the field has progressed 'from bench to bedside'. Abatacept [cytotoxic T-lymphocyte antigen-4 (CTLA-4)-immunoglobulin (Ig) (CTLA-4-Ig)], an inhibitor of CD28-mediated T-cell costimulation, was approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
124
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 93 publications
(111 reference statements)
1
124
1
1
Order By: Relevance
“…First, we report that abatacept inhibited T cell priming, which is consistent with previous in vivo studies showing that abatacept reduced T cell proliferation and proinflammatory cytokine levels (21). Importantly, we showed that abatacept treatment during priming did not induce functional anergy of T cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, we report that abatacept inhibited T cell priming, which is consistent with previous in vivo studies showing that abatacept reduced T cell proliferation and proinflammatory cytokine levels (21). Importantly, we showed that abatacept treatment during priming did not induce functional anergy of T cells.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm the ability of abatacept to inhibit T cell priming (21,22), we investigated the activation status of T cells derived from the draining LNs of nonimmunized (naive), primed, primed and treated with abatacept or control IgG, and orally tolerized mice and analyzed the expression of CD44, CD62L, ICOS, and CD71 (Figure 1). Abatacept reduced the proportion of activated T cells (CD44 high CD62L-) and inhibited the up- Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…T cell activation and proliferation are important factors in the initiation and perpetuation of arthritis. The possibility of treating arthritis by interfering with the interaction between the costimulatory molecules CD28 on T cells and CD80 (B7-1) and CD86 (B7-2) on APCs has raised interest in the field of rheumatology (111,112). CTLA-4 (CD152) is a homolog of CD28.…”
Section: From Animal Models Toward the Clinicmentioning
confidence: 99%
“…Thus, inhibition of T cell activation may lead to clinical benefits in patients with PsA. Full antigen-induced activation of naive T cells requires 2 discrete signals from the antigen-presenting cell (23). Antigen is presented to the T cell receptor in the context of a major histocompatibility complex molecule, but full activation occurs only when the binding of CD80 or CD86 to the CD28 molecule on the T cell produces a second costimulatory signal.…”
mentioning
confidence: 99%